Assessing Students' Speaking Ability Using Communicative Language Testing Approach on Secondary Level in the Pandemic Era - Ratu Erlinda Kurniatillah; Zwyna Rafika; Nida Husna; Didin Nuruddin Hidayat; Fitriah Fitriah (Universitas Pahlawan Tuanku Tambusai, 2022)
The objectives of this study are: (1) to find out what types of speaking skills in the communicative language testing approach do the teachers use on the secondary level; (2) and to find out which of the five types of speaking skills on the communication language test were most used by teachers during the pandemic. This study used the descriptive qualitative method. Respondents of this study were English teachers at the secondary level in Jakarta, which consisted of 20 teachers. The results of this study indicate that: first, the English teacher only uses performance to assess students' speaking ability in this pandemic era. Second, Assessing Students' Speaking Ability Using Communicative Language Testing Approach on a Secondary Level in the Pandemic Era is only carried out during the initial assessment stage and formative test. The implementation of the assessment of students' speaking abilities using a Communicative Language Testing Approach was applied when the teacher asked students to build a response or performance that is not just providing information. The teacher asks students to solve specific case problems (problem-solving). The teacher asks students to select the correct response that requires information and concepts so that they are more active in class because they must be able to bring information to solve problems based on the learning material that has been previously delivered. Third, teachers' perceptions are assessment using Communicative Language Testing is very good for improving students' speaking ability because students clearly show their work. Students can convey their ideas without fear. Students not only understand the theory but practice it in real life. On the other hand, the use of authentic assessment takes a long time.